The effect of Al on the oxidation behavior of Mo-6Si-12B-(1, 2, 4, 8)Al alloys. (November 2022) - Liu, Longfei; Shi, Chunchang; Zhang, Chenyu; Su, Ranran; Zhang, Hongliang; Voyles, Paul M.; Perepezko, John H.
Abstract: The isothermal and cyclic oxidation behavior of Mo-6Si-12B-(1, 2, 4, 8)Al samples was investigated from 800 to 1300 ℃. With increasing Al content, the isothermal oxidation resistance is enhanced and the pesting behavior is suppressed at 800 ℃. The Mo-6Si- 12 B– 4 Al alloy with an oxide layer of both an alumino-borosilicate glasses and mullite has the best overall oxidation performance. An oxidation kinetics model was developed based upon the contributions of the individual phase oxidation rates weighted by their relative amounts and sizes that provides a good account of the oxidation behavior. Highlights: With increasing Al content, isothermal oxidation resistance is enhanced but the cyclic oxidation resistance is degraded. A model was developed to analyze the transient oxidation stage of Mo-Si-B-Al alloys. The mullite/Al-doped borosilicate glass interface is characterized by atomic resolution transmission electron microscopy.